La carrière cancéreuse des enfants malades - Hélène Lecompte (Anthropologie & Santé)
When children are diagnosed with cancer, they are removed from their usual social spaces for a long period of time to be treated in the hospital, a place where they live, experience, and learn. How does one become a child with cancer? How does one become a “cured” child? What is the work of self-transformation undertaken by and in the hospital and what are long-term dispositions acquired? Based on ethnographic research, this article analyzes the experience of children from the first symptoms to the cancer after-life, using the concept of career. It describes the child’s cancer career and its different phases: the entry into the career, the way children are engaged in it, life in the hospital institution and the maintenance of the career despite the end of treatment. By understanding the process, from the first symptoms to the after-cancer, we also analyze how the experience of cancer and hospital contributes to shape former sick children’s self-identity.